KAJIAN AUTEKOLOGI HARAO Areca vestiaria Giseke PADA HUTAN DATARAN RENDAH DI KAWASAN TAMAN NASIONAL LORE LINDU (TNLL) SULAWESI TENGAH - Risma Risma; Wahyu Harso; Ramadanil Ramadanil (Biology Department, Mathematics and natural science, Tadulako University, 2019)
Areca vestiaria Giseke is an endemic palm and the main component of tropical rain forest in Wallacea region. The study of autecology of A. vestiaria at the lowland forest has never been done. This study was aimed to observe the biotic and abiotic factors surround the habitat A. vestiaria.. The results indicated that there were a number of plants growing surrounding A. vestiaria, but the highest important Value Index at the level tree, sapling, pole and seedling was Polyalthia glauca Boerl. with the IVI 59.04%, Semecarpus forstenii Blume. (66.90%), Polyalthia glauca Boerl. (82.95%) and Arenga undulatifolia (32.92%), respectively. Ordo Hymenoptera and Lepidoptera insects found on A. vestiaria during the observation time. Soil at observed area had pH value of 6.9 while N, P and organic matter concentration in the soil were 0.40%, 4.46 mg/g and 7.22%, respectively. Areca vestiaria grew under light intensity of 1005.5 lux, humidity of 89.3% and average daily temperature of 24.7%.